2009
DOI: 10.1111/j.1398-9995.2009.01946.x
|View full text |Cite
|
Sign up to set email alerts
|

Ozone exposure and its influence on the worsening of childhood asthma

Abstract: The prevalence of childhood asthmatic symptoms was about 4% higher at the high O(3) site than at the low O(3) site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 30 publications
2
6
0
Order By: Relevance
“…The lowest average daily surface ozone concentrations also occurred in 2007 (average concentration =92.10 μg/m 3 , varying between 39.38 μg/m 3 and 150.46 μg/m 3 ). In fact, as detected by other authors [32], surface ozone levels during the 2007 summer were among the lowest in the past decade in Portugal, and, accordingly, the number of exceedances in Europe was also lower in that summer than in any of the last 10 summers. The levels of the other pollutants tend to be low.…”
Section: Resultssupporting
confidence: 62%
“…The lowest average daily surface ozone concentrations also occurred in 2007 (average concentration =92.10 μg/m 3 , varying between 39.38 μg/m 3 and 150.46 μg/m 3 ). In fact, as detected by other authors [32], surface ozone levels during the 2007 summer were among the lowest in the past decade in Portugal, and, accordingly, the number of exceedances in Europe was also lower in that summer than in any of the last 10 summers. The levels of the other pollutants tend to be low.…”
Section: Resultssupporting
confidence: 62%
“…Daily variations in NO2 concentrations boiled down to two significant peaks -one in the morning and another at the end of the afternoon, matching the two traffic rush periods, as expected for urban areas (Wichmann et al, 2010). From the O3 outdoor profiles, it is possible to observe the highest concentrations along the afternoon, as expected (Sousa et al, 2009). These profiles were generally similar to those typically found indoors, thus outdoor air seemed to be the main contributor to those concentrations found indoors.…”
Section: Co No2 and O3supporting
confidence: 70%
“…Monteiro et al (2005) developed and validated a numerical air quality operational forecasting system over Portugal during the summer 2003 and noted that still improvements are needed on the chemistry-transport model. Sousa et al (2009b;2011) observed that occurrence of childhood asthmatic symptoms were significantly higher at sites with high surface O 3 values than at sites with low surface O 3 values.…”
Section: Introductionmentioning
confidence: 99%